Fallow management potentials of sesbania pachycarpa dc.: the green manure effects on amaranthus cruentus l. in ibadan, south western nigeria (2017)
Sown fallow with nodulating legume shrubs has been identified as an alternative in improving soil fertility. The green manure potential of Sesbania pachycarpa on the performance of Amaranthus cruentus were studied in pot and field experiments in Ibadan, Nigeria. Sesbania pachycarpa seedlings were grown in pots for 0 (control), 15, 30, 45, 60 and 75 days, and on field for 0, 30, 45 and 60, before incorporating into the soil to assess the Green Manure (GM). Three weeks after incorporation, Amaranthus cruentus was grown on the soil for six weeks. The performance of A. cruentus was assessed with Plant Height (PH), Stem Diameter (SD) and Number of Leaves (NL). The pot and field experiments were CRD and RCBD, respectively with three replicates. Data were analysed using descriptive statistics and ANOVA at a0.05- In the pot trial, the performance of A. cruentus [PH (45.30±0.8 cm), SD (0.6±0.1 cm), NL (18±0.3)] were highest in 45-Day GM. The field results followed the same trend with PH (46.30+1.2 cm), SD (0.8+0.1 cm) and NL (19.3±0.7) of A. cruentus highest in 45-Day GM. Turning in the plant grown for a minimum of 45 days improved performance of Amaranthus cruentus.